(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: No previous studies have documented changes in salivary secretion in patients with malaria. This study aimed to compare salivary secretion and composition in malaria positive and malaria negative individuals. Ninety participants composed of 40 malaria parasite positive and 50 malaria parasite negative individuals (age and gender matched) were included. Malaria diagnosis was achieved by microscopic examination of Giemsa stained thick and thin film of blood smears. A self-administered questionnaire was used to assess presence or absence of oral symptoms in the malaria parasite positive individuals. Whole saliva samples were collected and analyzed for flow rate, pH, total protein and concentrations of electrolytes (K+, Na+, Ca2+, Cl-, PO42- and HCO32-). Data were analysed using Independent-Samples t-test and Spearman’s correlation test. The salivary flow rate was significantly reduced in malaria parasite positive individuals (P = 0.001). Oral symptoms were present in 82.5% of the malaria parasite positive individuals. There was no significant difference in the salivary pH, total protein and electrolyte ion concentrations between the two groups. Also, Spearman’s correlation test showed no significant relationship between the presence of oral symptom and the salivary parameters. Salivary flow rates are reduced in the individuals with malaria. However, presence of oral symptoms in these individuals may not be attributed to the reduced salivary flow rate. Further studies are needed to validate our findings and elucidate mechanisms involved.